analisis Analisis Manajemen Pemeliharaan Alat Kesehatan Di Rumah Sakit X - Media Veni; Boy S Sabarguna; Arief Wahyudi (Jurnal Kesehatan Komunitas, 2020)
The implementation of public health which carried out in hospitals is determined by the provision of health care facilies, especially medical devices. To maintenance the properimplementation it needs to be supported by the amount of human resources, costs, infrastructure, Standard Operating Procedures for maintenance of medical devices and using MFK 8 as a guide. The problem found in this study is in case of carrying out the maintenance of medical devices not using the hospital accreditation standard. The purpose of this study is to know the management of medical device in hospital X. This research was a qualitative method. This research was conducted in August-September 2018. The informant in this study were 6 people who were taken based on the principle of sufficiency. Data processing used Triangulation. Data analysis used content analysis. The results showed that the maintenance of medical devices had not optimally due to lack of human resources and also constrained bycosts so that it had an impact on the availability of infrastructure in the hospital and the incomplete Standard Opertiang Procedures for medical devices. There was no inventory list and risk identification. There was not found evidence of medical equipment regularly checking. Should be doing the test of the function of each medical devices when buy them. Already doing a preventive and calibration maintenance program. Do not have technicians (ATEM) to carry out maintenance of medical devices. Keywords : ATEM, MFK 8, Resources